The Effects of Feed Restriction and Isolated or Group Rearing on the Measurement of Individual Feed Intake and Estimation of Feed Conversion Ratio in Juvenile Nile Tilapia (Oreochromis niloticus) for Selective Breeding Purposes - Rodde, Charles; Vandeputte, Marc; Trinh, Trong Quoc; Douchet, Vincent; Canonne, Marc; Benzie, John A. H.; de Verdal, Hugues (Frontiers in Genetics, 2021)
Accurately measuring the phenotype at the individual level is critical to the success of selective breeding programs. Feed efficiency is a key sustainability trait and is typically approached through feed conversion ratio (FCR). This requires measurements of body weight gain (BWG) and feed intake (FI), the latter being technically challenging in fish. We assessed two of the principal methods for measuring feed intake in fish over consecutive days: 1) group rearing 10 fish per group and video recording the meals and 2) rearing fish individually on a restricted ration. Juvenile Nile tilapia (Oreochromis niloticus) from the Genetically Improved Farmed Tilapia (GIFT) strain and the Cirad strain were entered into the study (128 GIFT and 109 Cirad). The GIFT strain were reared over three consecutive periods of seven days each under different feeding, recording and rearing scenarios i) in groups fed an optimal ration (g100) or ii) fed a 50% restricted ration (g50) both with video records of all meals and iii) reared in isolation and fed a 50% restrictive ration. The Cirad strain were tested similarly but only for scenarios i) and iii). All fish were fed twice daily with a calculated ration. Correlations showed the same trends for the GIFT and the Cirad strains. For the GIFT strain, correlations were positive and significant for BWG and FI measured in scenarios i) and ii), 0.49 and 0.63 respectively, and FI measured in scenarios i) and iii) (0.50) but not for BWG measured in scenarios i) and iii) (0.29, NS). The phenotypic correlation estimated for FCR between scenarios i) and ii) with fish fed an optimal or a 50% restricted ration was low and not significant (0.22). Feed Conversion Ratio for GIFT fish reared in groups or in isolation and fed with a restricted ration (scenarios ii) and iii)) were not significantly correlated either. Social interactions between fish, potentially impacting their efficiency, may explain the results. Therefore, selective breeding programs seeking to improve feed efficiency will need to carefully plan the feeding rate and the rearing system used to estimate FCR in order to optimise selection for the targeted production system.